Microarray screening reveals two non-conventional SUMO-binding modules linked to DNA repair by non-homologous end-joining. Issue 8 (14th April 2022) - Cabello-Lobato, Maria Jose; Jenner, Matthew; Cisneros-Aguirre, Metztli; Brüninghoff, Kira; Sandy, Zac; da Costa, Isabelle C; Jowitt, Thomas A; Loch, Christian M; Jackson, Stephen P; Wu, Qian; Mootz, Henning D; Stark, Jeremy M; et al.
Abstract: SUMOylation is critical for numerous cellular signalling pathways, including the maintenance of genome integrity via the repair of DNA double-strand breaks (DSBs). If misrepaired, DSBs can lead to cancer, neurodegeneration, immunodeficiency and premature ageing. Using systematic human proteome microarray screening combined with widely applicable carbene footprinting, genetic code expansion and high-resolution structural profiling, we define two non-conventional and topology-selective SUMO2-binding regions on XRCC4, a DNA repair protein important for DSB repair by non-homologous end-joining (NHEJ). Mechanistically, the interaction of SUMO2 and XRCC4 is incompatible with XRCC4 binding to three other proteins important for NHEJ-mediated DSB repair. These findings are consistent with SUMO2 forming a redundant NHEJ layer with the potential to regulate different NHEJ complexes at distinct levels including, but not limited to, XRCC4 interactions with XLF, LIG4 and IFFO1. Regulation of NHEJ is not only relevant for carcinogenesis, but also for the design of precision anti-cancer medicines and the optimisation of CRISPR/Cas9-based gene editing. In addition to providing molecular insights into NHEJ, this work uncovers a conserved SUMO-binding module and provides a rich resource on direct SUMO binders exploitable towards uncovering SUMOylation pathways in a wide array of cellular processes.